Investigating the Banking Sector Development Transmission Mechanism of Financial Development to Growth: Evidence from Sub-Saharan Africa (SSA) - Okoli, Tochukwu Timothy; Oluwafisayomi, Ajibola Rhoda (Journal of Economics and Behavioral Studies, 2019)
The search for financial development’s transmission channel to growth has always been updated in the literature. While there has not been a consensus on this matter, empirical findings on finance-growth nexus have been ambiguous. Relying on this, we investigate its bank development transmission channel to growth in a panel of twenty-eight Sub-Saharan Africa (SSA) countries from 2000-2016. Having adopted the augmented Solow (1956) and Mankiw et al. (1992) growth model, the fixed effect and dynamic system GMM estimation techniques reveals a negative non-significant and positive significant direct impact of finance on growth in the static and dynamic models respectively, thereby suggesting institutional (dynamic) factors that can spur finance. Secondly, the non-linear effects of bank development had a direct positive significant impact on growth and its marginal-effects before and after the financial crisis of 2007/08 were relatively stable. This implies that banks in SSA were relatively stable in financial intermediation; therefore SSA countries need to reinforce and improve its banking policy through FinTechs adoption. Finally, the interaction between bank development and financial development significantly increase steady-state growth. This implies that SSA economies can promote steady-state growth from financial development only when a threshold of bank development is reached.